STUDY OF THE BIOSORTION OF RED ACID 18, BLUE BASIC 99 AND BASIC YELLOW 57 PRESENT IN THE HAIR DYES WITH RESIDUES OF TEA LEAVES GREEN - Luciano Bellatin, Oscar Herrera (2014)
The use of waste green tea leaves (TV) with particle diameter 30 and 40 of the Tyler series, on the removal of the dyes basic yellow 57 (AM 57), basic blue 99 (AZB 99) and acid red 18 was investigated from aqueous solutions at room temperature by intermittent desorption experiments. The parameters evaluated in the adsorption capacity were: pH, mass of adsorbent, the concentration of dye adsorption rate and ionic strength, supported by the FTIR, SEM, EDX and TGA analysis. The results are analyzed using mathematical models of Langmuir, Freundlich, Temkin, Dubinin- Radushkevich and Redlich -Peterson. The results show that the adsorption is given by a mixed mechanism. The determined parameters show a high affinity of the adsorbent with AZ 99 with a maximum adsorption capacity of 287.2 mg g- 1, followed with by AM 57 120 mg g -1 and the RA 18 with 58 mg g- 1 elucidating the potential use of the adsorbent for the removal of the dyes in aqueous solutions by pseudo- second order kinetic. High concentration of the ionic strength decreases the adsorption of the three dyes.